2020
DOI: 10.1007/s40368-020-00576-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal knowledge on early childhood caries and barriers to seek dental treatment in Jordan

Abstract: Purpose To assess maternal knowledge, attitudes and beliefs of Early Childhood Caries (ECC) risk factors and to determine barriers in seeking dental treatment among children with ECC. Methods A total of 600 mothers of healthy children, aged 3–5 years, with ECC attending maternity and child health centres in Jordan completed a questionnaire using face-to-face interviews. ECC was diagnosed clinically by the chief investigator, based on the diagnostic criteria suggested by American Academy of Paediatric Dentistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 18 publications
4
23
2
2
Order By: Relevance
“…Regarding the statement “It is better to use fluoride toothpaste when brushing children’s teeth”, only 52% of parents answered “true”, while only 42% agreed with the statement “Protecting child’s teeth with fluoride”. These findings are consistent with those BaniHani et al’s study [ 36 ], and affirms that parents’ knowledge remains theoretical and not operational. This should be highlighted because using fluoride toothpaste is one of the most effective ways to prevent early caries in children.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the statement “It is better to use fluoride toothpaste when brushing children’s teeth”, only 52% of parents answered “true”, while only 42% agreed with the statement “Protecting child’s teeth with fluoride”. These findings are consistent with those BaniHani et al’s study [ 36 ], and affirms that parents’ knowledge remains theoretical and not operational. This should be highlighted because using fluoride toothpaste is one of the most effective ways to prevent early caries in children.…”
Section: Discussionsupporting
confidence: 93%
“…Most of the enrolled children were preschoolers (average 4.8 years) and the percentage of boys in the study was slightly higher than girls. The average dmft score identified in our study was comparable to that revealed in a recent study that was conducted by Bani Hani et al in Jordan, 6.04 ± 1.2 [ 14 ]. However, it was higher than that detected in regional and neighboring countries.…”
Section: Discussionsupporting
confidence: 89%
“…This result is in concordance with findings from different parts of the world [ 23 , 27 , 28 ]. Bani Hani et al assessed the association between maternal knowledge and childhood caries in Jordan, and low family income constituted a significant barrier to seek dental treatment [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Awareness concerning children's dental health has been evaluated inseveral studies which show a limited knowledge of caries preventive measures among parents [3,[35][36][37][38]. According to El Karmi et al, only 16% of expectant mothers taking part in the survey thought that primary teeth need brushing [38].…”
Section: Consequencesmentioning
confidence: 99%